EARLY–MIDDLE FORMATIVE PERIOD SUBSISTENCE IN THE TEOTIHUACAN VALLEY, MEXICO: PRE-HISPANIC PLANT REMAINS FROM ALTICA. Issue 2 (2019) - McClung de Tapia, Emily; Acosta-Ochoa, Guillermo; Martínez-Yrizar, Diana; Adriano-Morán, Carmen Cristina; Cruz-Palma, Jorge; Chaparro-Rueda, Berenice
Abstract: Recent excavations at the Early–Middle Formative period site of Altica in the southern piedmont of the Teotihuacan Valley, Mexico, provide evidence for early agriculture and plant use in a rural community in the northern Basin of Mexico. In the Basin of Mexico, settled agricultural communities were present in the southern sector of the region from at least 1200 calb.c. Initial expansion into the semiarid northern sector of the Basin, however, appears to have taken place towards the end of the Early Formative, during the transition to the Middle Formative when agricultural economies based on maize cultivation became firmly established, setting the scene for increased population density and concomitant social complexity. Altica is currently the only community in the Teotihuacan Valley spanning this transitional period that has survived in the face of intensive changes in land use over the last three millennia. Macro- and microbotanical evidence recovered from radiocarbon-dated excavated contexts at Altica provide evidence for maize cultivation and suggest a subsistence economy in transition, prior to the establishment of intensive dependence upon a broader range of domesticated and cultivated plants.